2014
DOI: 10.4067/s0717-97072014000100009
|View full text |Cite
|
Sign up to set email alerts
|

IODINE CATALYZED CASCADE SYNTHESIS OF FLAVONE DERIVATIVES FROM 2'-ALLYLOXY-α, β-DIBROMOCHALCONES

Abstract: Synthesis of flavones from 2'-allyloxy-α, β-dibromochalcones has been described. The iodine induced oxidative cyclization of 2'-allyloxy-α, β-dibromochalcones results into the formation of 3-bromoflavanones which ultimately gives flavones. Dehydrobromination of 3-bromoflavanone to give flavone is the preferred reaction over dehydrogenation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 4 publications
(4 reference statements)
0
10
0
Order By: Relevance
“…Therefore, in the first set of reactions, several substituted THβC (3a-3f) were evaluated, and it was found that the substrates which hold O-allyl group at meta position of phenyl ring afforded 6c in 65-70% yields. Next, we investigated the substrates 3g, 3h, 3i, and 3j ( Further, we extended our investigation toward the selective deallylation followed by dehydrogenation of Oallyl THβC; As per our previous report [19,20] , we have found that deallylation proceed by using molecular iodine in DMSO+H + (20 mol %) at 60 C and optimized condition in our hand (Table 1, entry 11). Thereafter, we have applied our previously developed protocol molecular iodine in DMSO/H + with 50 and 100 mol% at 90 C; it was observed that the aromatization of O-allyl-tetrahydoβ-carboline 3a, 3b, and 3g (Table 2, entry 11, 12) gave 4a, 5a with 75-80% yield with deallylation (Table 2, entry 11,12).…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Therefore, in the first set of reactions, several substituted THβC (3a-3f) were evaluated, and it was found that the substrates which hold O-allyl group at meta position of phenyl ring afforded 6c in 65-70% yields. Next, we investigated the substrates 3g, 3h, 3i, and 3j ( Further, we extended our investigation toward the selective deallylation followed by dehydrogenation of Oallyl THβC; As per our previous report [19,20] , we have found that deallylation proceed by using molecular iodine in DMSO+H + (20 mol %) at 60 C and optimized condition in our hand (Table 1, entry 11). Thereafter, we have applied our previously developed protocol molecular iodine in DMSO/H + with 50 and 100 mol% at 90 C; it was observed that the aromatization of O-allyl-tetrahydoβ-carboline 3a, 3b, and 3g (Table 2, entry 11, 12) gave 4a, 5a with 75-80% yield with deallylation (Table 2, entry 11,12).…”
Section: Resultsmentioning
confidence: 79%
“…[19] The substoichiometric amount of I 2, in DMSO has been used for the cascade synthesis of flavones. [20] The iodine in DMSO at 130 C, it prefers deprotection of allyl group carboxylic ester [21] and direct C-deallylation of allyl group from the active methylene position [13] along with chemoselective oxidative dehydrogenation of allyloxy substituted β-anilinodihydro-chalcones to β-anilino-chalcones [22] was preferred reaction over deallylation (Figure 2). The Significant biological properties of βcarboline makes it synthetically important Unit.…”
Section: Introductionmentioning
confidence: 99%
“…The use of iodine in the dimethylsulfoxide reagent to produce 2'-allyloxy-, -dibromochalcones (5), which lead to the equivalent 3-bromoflavones (6). When 2'-allyloxy chalcones were treated with DMSO-I2 reagent, the allyl group was removed easily, followed by cyclization and dehydrogenation, yielding flavones (7) [10].…”
Section: From 2'-allyloxy-α β-Dibromochalconesmentioning
confidence: 99%
“…1) (1)(2)(3). Although both glycosides are naturally occurring in the families of Rutaceae, Lamiaceae, Apiaceae, Scrophulariaceae (S. nadosa) (2)(3)(4)(5)(6)(7)(8)(9)(10), the industrial sector uses semisynthetic diosmin derived from hesperidin by a suitable oxidation reaction (I 2 /pyridine, I 2 /dimethylsulfoxide or other) (1)(2)(3)11,(15)(16)(17)(18). Hesperidin is most commonly isolated from dry orange or citrus peels (Citrus sinesis, L., Citrus aurantium, L., Citrus lemon, L., and other Citrus species) (3,8,10).…”
Section: Structure Sources and Isolationmentioning
confidence: 99%